Importance of Nutrition: rst 1,000 days of life - López Robles, Gabriela Alejandra; González Hernández, Norma; Prado López, Lidia María (Acta Pediátrica Hondureña, 2019)
The attention during the first 1000 days is the essential key to a healthy future life, as this subgroup of the population is prone to dietary disequilibrium and insuficiencies. It’s of vital importance, a correct nutrition during the first thousand days, to support an adequate growth and development. Besides, it’s important to control nutritional disorders that occur during gestation and in the first two years of life, which subsequently increase morbi-mortality, as it permanently impacts on the health of the individual. In the last years, there’s been a considerable interest in the effects of excessive weight gain during childhood, due to the fact that the development of fatty tissue during this period is a determinant factor of an adult corporal composition. Breastmilk is a unique and irreplaceable aliment, because it provides all the nutrients that guarantee an adequate development. WHO recommend it during the first 2 years. Pediatricians mission during this phase of life is to promote exclusive breastfeeding so that the risk of infectious, immunologic and chronic diseases decreases. This is why pediatrician’s role is to protect, promote and support breastfeeding. The 1000 days clock cannot be reset, so we have to be futurist and have the adequate knowledge about feeding in this important period. Keywords Nutrition, Breastfeeding, proteins of high biological value, essential amino acids, iron deficiency anemia faith